Tooth flank fracture – An applied fatigue study of case hardened bevel gears. (February 2022) - Böhme, Stephan André; Szanti, Gabor; Keski-Rahkonen, Joni; Komssi, Tami; Santaella, José Garcia; Vinogradov, Alexei
Highlights: Application of developed material, stress and multiaxial fatigue model to a set of bevel gear tests. Accurate failure prediction of the majority of wheel-initiated tooth flank fractures. Methodology capable of differentiating and predicting surface and subsurface fatigue in gears. Fractographic analysis of subsurface failures, revealing elongated MgO-Al2 O3 cluster in initiation site. Proposal of a reiterated lifetime factor based on the Maximum Likelihood Method. Abstract: A material model for carburized CrNiMo steel and an advanced shear stress intensity, multiaxial fatigue criterion against surface and subsurface fatigue in bevel gears have been developed and presented in earlier publications. This study assesses the accuracy of the proposed methodology by comparing it to load-controlled bevel gear tests at varying hardening layer thicknesses. The dominant failure mode was wheel-initiated tooth flank fracture. Fractographic analysis by means of scanning electron microscopy revealed a severely elongated MgO-Al2 O3 cluster in the only pinion-initiated tooth flank fracture. By correlating the calculated material utilizations and the number of cycles to failure, a reiterated lifetime factor is presented. The refined methodology is shown to be capable to differentiate between and accurately predict pitting and subsurface fatigue under well-defined test conditions.